Avaliação de parâmetros sanguíneos, como marcadores de prognóstico, em cães infectados naturalmente por Leishmania infantum submetidos ao tratamento com imunoterapia vacinal associada ao alopurinol - Flávia Carvalho Bitencourt de Oliveira (2017)
Canine visceral leishmaniasis is a chronic disease caused by L. infantum wich affects dogs and promotes serious injury leading to death. Dogs are the main reservoir of this parasite, having a central role in the transmission to humans. In Brazil canine visceral leishmaniasis have been treated for more than fifteen years. There are several protocols for treatment around the world. Recently, a new treatment protocol has been proposed using immunotherapy with Leistech® vaccine, associated with allopurinol. However, there are no reliable parameters of prognosis for clinical recovery in dogs. This study aimed to characterize parameters from blood as biomarkers in dogs naturally infected and treated in order to use this data as prognosis and therapeutic management. The study included dogs naturally infected by Leishmania infantum, symptomatic and treated with immunotherapy and allopurinol. Medical records containing information on the clinical status, hematological and biochemical tests were analyzed. Our results showed improvement in some clinical parameters evaluated. The data set obtained in this study indicates that monocytes and plateletes may represent important parameters of disease prognosis and treatment, acting as biomarkers, thus improving the therapeutic approach, avoiding risks and unnecessary costs and providing better animal benefits.